Pemanfaatan Minyak Pirolisis Ban Bekas Menjadi Bahan Bakar Alternatif - Saputra, Ade; Mangalla, Lukas Kano; Salimin, Salimin (Teknik Mesin Universitas Halu Oleo, 2022)
Tire production in Indonesia is increasing continuously in line with the increasing automotive industry. Along with that, the waste of used tires that are not used in the environment is increasing. So we researched the use of used tire pyrolysis oil as an alternative fuel. The purpose of this study was to determine how to produce fuel oil through the pyrolysis process of used motorcycle tires and to determine the combustion characteristics of the pyrolysis results of motorcycle-used tires. The method used in this research is an experimental method using a pyrolysis tool and data collection is carried out directly with various temperature variations. The research was conducted at temperatures of 250oC, 300oC, and 350oC to produce 202 ml, 280 ml, and 219 ml of pyrolysis liquid, respectively. The pyrolysis oil combustion test produced shows that the burning of used tire pyrolysis oil takes longer than the burning of kerosene in the same volume. Keywords: Tires, pyrolysis, temperature